FRI0569 To what extent is interobserver reliability for detecting ultrasound urate crystal deposits dependent on the experience of the ultrasonographer?. (12th June 2018) - Uson, J.; Garmendia, E.; Moragues, C.; de Agustin, J.J.; Mayordomo, L.; de Miguel, E.; Corominas, H.; Garrido, J.; Naredo, E.
Abstract : Background: Musculoskeletal (MS) ultrasound (US) is used for diagnosing and managing gout in clinical practice and has the potential to become an outcome measure for clinical trials. Cartilage double contour sign (DC) and tophi(T) are elementary US lesions of urate crystal deposits. OMERACT MSUS Working Group developed the first consensus-based definitions for DC and T and showed that the reliability of the definitions ranged from moderate to excellent in static images and somewhat lower in patients when tested in highly experienced MS ultrasonographers. 1 Objectives: To compare the agreement between a group of rheumatologist-ultrasonographers (RU) with a variable experience in MSUS with the agreement between rheumatologist-ultrasonographers highly experienced in MSUS and teachers (ExRU) for detecting DC and T in in patients. Methods: 16 RU with a variable experience in MSUS were trained in the OMERACT U definitions for DC and T. Next, as a preliminary reliability exercise, they read 30 different US joint static images from gout patients and healthy subjects for the presence or absence of DC or T. Afterwards the RU group and a group of 5 ExRU consecutively, independently and blindly carried out each a reliability exercise in 5 subjects (3 crystal proven gout patients and 2 healthy controls) for the presence or absence of DC or T. Both groups performed a standardised 8 min bilateral grey-scale UU examination of the following: the suprapatellar knee recess for T, femoral knee cartilage for DC, medial and lateral knee compartments for T and dorsal first metatarsal phalangeal for T and metatarsal head for DC. Fleiss kappa was used to assess interobserver reliability. K values 0–0.20 were considered poor; 0.20–0.40 fair;0.40–0.60 moderate;0.60–0.80 good and 0.80–1 excellent. Results: Kappa values were moderate for the RU group inter-reader agreement in static US images (K 0.514 for DC and 0.465 for T). However, there were significant differences between the interobserver agreement from both groups in patients, being kappa values fair (K 0.344 for DC and 0.305 for T) for the RU group while good for the ExRU group (K 0.674 for DC and 0. 673 for T) (p<0.001 for DC and T). Worst agreement among RU and ExRU was for detecting DC in MTF joint. Conclusions: This study showed that although inter-reader agreement for gout lesions can be acceptable in static US images, interobserver agreement in patients is highly dependent on the experience of the ultrasonographers. Reference: [1] Terslev L, Gutierrez M, Schmidt WA, Keen HI, Filippucci E, Kane D, et al. Ultrasound as an Outcome Measure in Gout. A Validation Process by the OMERACT Ultrasound Working Group. J Rheumatol2015;2149–54. Acknowledgements: Carlos Salgado from GE heathcare, Ultrasonidos Iberia. Disclosure of Interest: None declared